Pelatihan Pembuatan Buket Snack untuk Meningkatkan Kreativitas Ibu-Ibu PKK Desa Prajegan Sukorejo Ponorogo - Alfida, Viqi Noor; Azizah, Suci Midsyahri (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The snack bouquet making training is a strategic initiative designed to enhance the creativity and skills of PKK (Family Welfare Empowerment) members, especially mothers. The program aims to introduce creative techniques in making a snack bouquet, which not only serves as a food presentation, but also as an aesthetic and value-added element in social events and celebrations. Through this training, participants will gain a practical understanding of how to select ingredients, preparation techniques, and decoration of an attractive and innovative snack bouquet. The training includes both theoretical and practical sessions, designed to provide basic knowledge as well as technical skills in snack bouquet making. Participants will learn about the different types of snacks that can be used, efficient arrangement techniques, and how to decorate the bouquet to make it look attractive and match the theme of the event. With this training, PKK women are expected to apply their new skills in various occasions, both for personal use and in social activities in their communities. The expected outcomes of the training include increased creativity in food preparation, development of decoration skills, as well as added aesthetic value in food presentation. In addition, the training aims to strengthen the spirit of gotong royong and togetherness among PKK members, as well as provide them with tools that can increase danceability.